Answer:
Multiply the first equation by 3 and multiply the second equation by -2.
This is justified by the multiplication property of equality
Explanation:
we have
----> first equation
----> second equation
step 1
Multiple the first equation by 3 both sides
-----> by multiplication property of equality
----> new first equation
step 2
Multiple the second equation by -2 both sides
-----> by multiplication property of equality
----> new second equation
step 3
Solve the system of equations by elimination
Adds new first equation and new second equation
![6x+15y=21\\-6x-8y=-12\\-------\\15y-8y=21-12\\7y=9\\y=(9)/(7)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jjtiix3panl2g2h73xkzwz3idb73ei4vii.png)
Find the value of x
substitute the value of y in any equation and solve for x
The solution is the point
![((2)/(7),(9)/(7))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jjj0ru9bkftcqljkzzql0x38sf3417kvh1.png)
therefore
Multiply the first equation by 3 and multiply the second equation by -2.
This is justified by the multiplication property of equality